Síntese identitária: uma proposta de formas de análise diferenciadas para a apreensão da identidade de santos populares - Souza, Régis de Toledo (2007)
The objective of this work is to present, describe and conceptualize what we called concept-object , a type of identity survey, on the research on identities in which we can not access directly one life s history as auto narrative. This concept resulted from research on the popular catholic devotion in Vale do Paraíba region of São Paulo State, Brazil. The structure of our work is divided as follows: the explanation of the concept s context, based on our field of study and aiming specifically data collected from cemeteries of the region. In the sequence we state the problem, based on the proposed concept, and finally we present the method to approach it. The proposal was elaborated from elements that in our understanding are associated to the concept and can contribute to its explanation. The data points towards the need to establish specific methods of analysis to deal with the understanding of the identity on extreme cases, like the devotion saints popular. The reason comes mainly from the fact that we lack reports from the very individuals that were designated as saints